Birth size, risk factors across life and cognition in late life: protocol of prospective longitudinal follow-up of the MYNAH (MYsore studies of Natal effects on Ageing and Health) cohort. Issue 2 (16th February 2017) - Krishna, Murali; Kumar, G Mohan; Veena, S R; Krishnaveni, G V; Kumaran, Kalyanaraman; Karat, Samuel Christaprasad; Coakley, Patsy; Osmond, Clive; Copeland, John R M; Chandak, Giriraj; Bhat, Dattatray; Varghese, Mathew; et al.
Abstract : Introduction: For late-life neurocognitive disorders, as for other late-life chronic diseases, much recent interest has focused on the possible relevance of Developmental Origins of Health and Disease (DOHaD). Programming by undernutrition in utero, followed by overnutrition in adult life may lead to an increased risk, possibly mediated through cardiovascular and metabolic pathways. This study will specifically examine, if lower birth weight is associated with poorer cognitive functioning in late life in a south Indian population. Methods and analysis: From 1934 onwards, the birth weight, length and head circumference of all babies born in the CSI Holdsworth Memorial Hospital, Mysore, India, were recorded in obstetric notes. Approximately 800 men and women from the Mysore Birth Records Cohort aged above 55 years, and a reliable informant for each, will be asked to participate in a single cross-sectional baseline assessment for cognitive function, mental health and cardiometabolic disorders. Participants will be assessed for hypertension, type-2 diabetes and coronary heart disease, nutritional status, health behaviours and lifestyles, family living arrangements, economic status, social support and social networks. Additional investigations include blood tests (for diabetes, insulin resistance, dyslipidaemia, anaemia, vitamin B12 and folate deficiency, hyperhomocysteinemia, renal impairment, thyroid disease and Apolipoprotein E genotype), anthropometry, ECG, blood pressure, spirometry and body composition (bioimpedance). We will develop an analysis plan, first using traditional univariate and multivariable analytical paradigms with independent, dependent and mediating/confounding/interacting variables to test the main hypotheses. Ethics and dissemination: This study has been approved by the research ethics committee of CSI Holdsworth Memorial Hospital. The findings will be disseminated locally and at international meetings, and will be published in open access peer reviewed journals.